The Influence of biofertilizer on abundance of Nitrogen Fixing bacteria and growth of Chinchona Plants (Chinchona ledreriana.) Clone Cib. 5 - Merry Antralina; Joko Santoso; Dewi Kania (Research Institute for Tea and Cinchona, 2015)
The objective of this research was to eva-luate the effect of biofertilizer on the abundance of nitrogen fixing bacteria and growth of cin-chona plants (Cinchona ledgeriana Moens) clones Cib.5. The research was conducted at the Research Institute for Tea and Cinchona, Gambung, Bandung, from May 2011 until June 2011. A randomized block design was used with five treatments and five replication. Application of five concentration of biofertilizer were per-formed. Concentrations were: 0, 2, 4, 6, and 8 cc/l of water. The results indicated that the application of biofertilizer gave the higher total bacterial population compared to the treatment without biofertilizer, but showed no significant effect on growth of Cinchona plants. Concen-tration of biofertilizer 8 cc/l gave the higher total bacterial population of nitrogen fixing.